Radiologic imaging of congenital gastrointestinal anomalies in infants - Leny Zabidi; Gatot Irawan Sarosa; Farah Prabowo (Paediatrica Indonesiana, 2012)
Background Congenital gastrointestinal anomalies may manifestsigns or symptoms in the first few days of life, most commonly inthe fonn of obstructions. Radiologic imaging plays an importantrole in diagnosis confirmation and surgical correction plans. Mostcases may be diagnosed by plain radiographs alone, but cr scansand MRI may be needed to make accurate diagnoses, especiallyin difficult cases.Objective To report radiologic imaging findings in infants Mthcongenital gastrointestinal anomalies.Methods For this retrospective, crossô€Šsectional study we tooksecondary data from medical records of infants 'With congenitalgastrointestinal anomalies in Dr. Kariadi Hospital, Semarang,Indonesia from January 2010 - June 2011. Diagnosis of congenitalanomalies was confirmed by clinical manifestation and radiologicimaging. Radiologic findings were reviewed by a single radiologiston duty at that time. Data is presented in the form of frequencydistribution.Results Subjects consisted of 50 males and 23 females. The mostcormnon complaints were vorrritingin 14 subjects (19%), alxlominaldistension in 31 subjects (43%), and fecal passage dysfunction in28 subjects (38%). Radiologic imaging of subjects with congenitalgastrointestinal anomalies revealed the folloMng conditions: analatresia in 28 subjects (38%), congenital megacolon in 21 subjects(29%), esophageal atresia in 14 subjects (19%), duodenal atresia in9 subjects (12%), and pyloric atresia in 1 subject (2%).Conclusion Using radiologic imaging of infants with congenitalgastrointestinal anomalies, the most to least common conditionsfound were anal atresia, congenital megacolon, esophagealatresia, duodenal atresia, and pyloric atresia. [Paediatr Indones.2012;52:341-5].